Morusin inhibits glioblastoma stem cell growth in vitro and in vivo through stemness attenuation, adipocyte transdifferentiation, and apoptosis induction. Issue 1 (31st December 2014) - Guo, Huijie; Liu, Chuanlan; Yang, Liuqi; Dong, Lihua; Wang, Li; Wang, Qiaoping; Li, Haiyan; Zhang, Jie; Lin, Ping; Wang, Xiujie
Abstract : Glioblastoma multiforme (GBM) cancer stem cells (GSCs) are responsible for the progression and recurrence of GBM after conventional therapy. Morusin possesses anti‐cancer activity in vitro. The purpose of this study is to confirm the growth inhibition effect of morusin on human GSCs growth in vitro and in vivo and to explore the possible mechanism of its activity. Human GSCs were enriched under nonadhesive culture system, and characterized through neurosphere formation, toluidine blue staining, immunofluorescence staining, Western blotting analysis of stemness markers of CD133, nestin, Sox2 and Oct4, and tumorigenecity in vivo; the growth inhibition effect of morusin on human GSCs in vitro and in vivo were tested by cell cytotoxicity, neurosphere formation inhibition, adipogenic differentiation, apoptosis induction, and tumor growth inhibition in vivo assays. The potential molecular mechanisms underlying the growth inhibition effect of morusin on GSCs in vitro and in vivo were investigated with Western blotting evaluation of stemness, adipogenic, and apoptotic proteins in morusin treated GSCs and tumor tissues. GSCs enriched under nonadhesive culture system possess stemness characterstics; Morusin inhibited GSCs growth in vitro and in vivo, it reduced stemness of GSCs, induced them adipocyte‐like transdifferention and apoptosis. Morusin has the potential to inhibit human GSCs growth in vitro and in vivo through stemness attenuation, adipocyte transdifferentiation, and apoptosis induction. © 2014 Wiley Periodicals, Inc.